The Cognitive Mechanisms in Music Listening Interventions for Pain: A Scoping Review. (6th April 2020) - Howlin, Claire; Rooney, Brendan
Abstract: Music interventions have been introduced in a range of pain management contexts, yet considerable inconsistencies have been identified across evaluation studies. These inconsistencies have been attributed to a lack of clarity around the prospective cognitive mechanisms of action underlying such interventions. The current systematic scoping review was conducted to examine the theoretical rationales provided in the literature for introducing music listening interventions (MLIs) in pain contexts. 3 search terms ( music, listening, and pain ) were used in four electronic databases, and 75 articles were included for analysis. Content analysis was used to identify that more intensive listening schedules were associated with chronic and cancer pain compared with procedural pain. The degree to which patients had a choice over the music selection could be categorized into 1 of 5 levels. Thematic synthesis was then applied to develop 5 themes that describe the cognitive mechanisms involved in MLIs for pain. These mechanisms were brought together to build the Cognitive Vitality Model, which emphasizes the role of individual agency in mediating the beneficial effects of music listening through the processes of Meaning-Making, Enjoyment, and Musical Integration. Finally, content analysis was used to demonstrate that only a small proportion of studies were explicitly designed to examine the cognitive mechanisms underlying MLIs and we have suggested ways to improve future practice and empirical research. We call on researchers to design and evaluate MLIs in line with the Cognitive Vitality Model of music listening interventions for pain.